(untitled) (Anclajes, 2018)
Released in 1915, Nobleza gaucha is the first blockbuster in Argentine film history. Per critical consensus, this success is largely due to the skilful way in which the movie partially adapts a set of texts from 19th century Argentine literature, among which stands out José Hernández’s Martín Fierro (1872 and 1879). Based on a comparative reading of the poem and the film, this article aims to investigate the ways in which the Pampas are addressed in the movie as both a landscape and a setting for national history. To that end, two kinds of images of the plains will be considered. On one hand, the figurations of the Pampas in the film, regarded as sublime images, are etched in a tradition from Río de la Plata culture that is more rooted in literature than in the visual arts. On the other hand, regarded as images-movement, these figurations produce an aesthetic inflection linked to the novelty of cinema and to the cultural, social and political changes Argentina faced in the first decades of the 20th century.